Peramalan Penjualan Pakaian Berbasis Web Menggunakan Metode Seasonal Adjustment - Hazrina, Umi Indah; Sembiring, Muhammad Ardiansyah; Amalia (Institut Teknologi Garut, 2025)
In an increasingly competitive industrial era, companies are required to produce quality products and manage inventory effectively to meet consumer needs. Toko Baju Manisem, a business engaged in the production and sale of clothing, faces challenges in determining optimal stock levels because it still uses manual methods to calculate inventory. This risks causing stock shortages or surpluses, which can lead to additional costs and potential losses. This study aims to develop a web-based sales forecasting system using the seasonal adjustment method to improve the accuracy of demand predictions. Seasonal adjustment is a time series data analysis technique that eliminates seasonal factors so that trend patterns are clearer and forecasts are more accurate. This system was built using the PHP programming language to facilitate the prediction process and more optimal inventory management. The results of this study show that the application of the seasonal adjustment method can improve efficiency in inventory management, reduce the risk of excess or shortage of goods, and help business owners make more informed decisions. With this system in place, it is hoped that Toko Baju Manisem can optimize its sales strategy and improve its business sustainability.